Crystal structure, computational studies, and stereoselectivity in the synthesis of 2-aryl-thiazolidine-4-carboxylic acids via insitu imine intermediate - Jagtap, Rohidas M.; Rizvi, Masood A.; Dangat, Yuvraj B.; Pardeshi, Satish K. (Journal of Sulfur Chemistry, 2016)
This article presents the synthesis of (2R/2S,4R)-2-aryl-thiazolidine-4-carboxylic acids via nucleophilic addition of L-Cysteine on aromatic aldehydes involving a yield and time-effective room temperature reaction in an aqueous DMSO medium in the presence of NaHCO3 as a base. The synthesized diastereomers were spectroscopically characterized and quantified for diastereomeric excess by liquid chromatography-mass spectrometry analysis. The impact of the type and position of substituent in aromatic aldehydes on reaction time, % yield, H-1 NMR shift at newly formed chiral center [C(2)-H], and diastereomeric excess (de%) have been investigated. A plausible mechanism for stereoselectivity via an in situ imine intermediate is proposed using real-time IR monitoring of the synthetic reaction based on the significant signals at 1597, 1593cm(-1) for imine (C=N) stretching. The imine mechanism for stereoselectivity was further supported by NMR studies of azomethine C-13 NMR signals at 159, 160ppm and by the single crystal structure of hitherto unknown (2S,4R)-3-(tert-butoxycarbonyl)-2-(2-hydroxyphenyl)thiazolidine-4-carbox ylic acid (3a) obtained as a major diastereomer in the synthesis of the butyloxy carbonyl (BOC) derivative of (2R/2S,4R)-2-(2-hydroxyphenyl)thiazolidine-4-carboxylic acid. The significant ortho-OH effect of phenolic hydroxyl group leading to strong hydrogen bondings plays a vital role in the formation of 2S,4R BOC derivative stereoselectively. The frontier molecular orbitals, possible electronic excitations, IR band characterizations, and reactivity parameters of newly reported compound (3a) have been predicted using quantum chemical descriptors from density functional theory. The theoretical exploration of experimental spectra using time-dependent DFT indicated a (-*) transition between HOMO and LUMO in the ultraviolet region.
Keywords: 2-aryl-thiazolidine-4-carboxylic acids; density function theory; frontier molecular orbitals; imine intermediate; X-ray crystal structure